An Exploration of Gendered Power Dynamics within Tribal Structures: A Case Study of South Waziristan - Ayesha Wazir (`, 2025)
This research explores gendered power relations in tribal formations in South Waziristan, a territory with entrenched patriarchal conventions and cultural values. In the face of worldwide trends towards equality between genders, tribal communities such as the one in South Waziristan continue to be relatively conservative. Traditional hierarchies of power within tribal codes influence and confine women’s roles and deny them agency in social, political, and economic life. This study uses qualitative approaches, such as interviews with indigenous residents and textual analysis of tribal norms (Pashtunwali), to explore how these systems perpetuate male supremacy and exclude women. The results demonstrate the integration of tradition, religion, and cultural identity in perpetuating gender inequalities. Recommendations stress the need for participatory policies, education, and community participation for slowly altering rooted gender dynamics. Keywords: Gender, Tribal Organization, South Waziristan, Pashtunwali, Patriarchy, Women, Power Relations